2023
DOI: 10.1186/s40885-022-00233-2
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and its associations with left ventricular diastolic function according to heart failure types

Abstract: Background Little is known about the characteristics of arterial stiffness in heart failure (HF). This study was performed to compare the degree of arterial stiffness and its association with left ventricular (LV) diastolic function among three groups: control subjects, patients with HF with reduced ejection fraction (HFrEF), and patients with HF with preserved ejection fraction (HFpEF). Methods A total of 83 patients with HFrEF, 68 patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…226 RAAS involves many aspects of CVD, from ED, inflammation, and oxidative stress in atherosclerosis and hypertension to myocardial remodeling with heart failure development. 227–229 RAAS blockage protects against ED and arrhythmia. 230 In addition to the RAAS, atherosclerosis and VC caused by various uremic metabolites play a role in arterial remodeling and a decrease of elasticity, inducing significantly increased systolic arterial blood pressure.…”
Section: The Deleterious Effects Of Metabolites and Aberrant Signalin...mentioning
confidence: 99%
See 1 more Smart Citation
“…226 RAAS involves many aspects of CVD, from ED, inflammation, and oxidative stress in atherosclerosis and hypertension to myocardial remodeling with heart failure development. 227–229 RAAS blockage protects against ED and arrhythmia. 230 In addition to the RAAS, atherosclerosis and VC caused by various uremic metabolites play a role in arterial remodeling and a decrease of elasticity, inducing significantly increased systolic arterial blood pressure.…”
Section: The Deleterious Effects Of Metabolites and Aberrant Signalin...mentioning
confidence: 99%
“…230 In addition to the RAAS, atherosclerosis and VC caused by various uremic metabolites play a role in arterial remodeling and a decrease of elasticity, inducing significantly increased systolic arterial blood pressure. 177,229 Moreover, ADMA/SDMA and UA also play an essential role in blood pressure regulation and hypertension development in patients with CKD, owing to their negative effects on bioactive NO elaboration 109,110,123 and consequent impaired vascular relaxation.…”
Section: The Deleterious Effects Of Metabolites and Aberrant Signalin...mentioning
confidence: 99%
“… 70 In a study conducted on Koreans by our research team with similar findings, baPWV was significantly increased in HFpEF patients with a history of hospitalization compared to the control group (1,909 vs. 1,661 cm/sec). 71 Reddy et al 72 assessed central aorta compliance by invasively obtaining radial artery waveforms in 98 patients with HFpEF and 22 patients with hypertension. The study findings indicated that HFpEF patients, when compared to hypertensive patients, exhibited reduced arterial compliance, which correlated with increased LV filling pressure.…”
Section: Arterial Stiffness As a Contributor To Hfpefmentioning
confidence: 99%
“…Имеются свидетельства вклада повышенной АР в развитие СН de novo [12], низкую переносимость физических нагрузок при СН, ассоциаций повышения каротидно-феморальной скорости распространения пульсовой волны (кфСРПВ) с сердечной недостаточностью с сохранной фракцией выброса (СНсФВ) [13]. В некоторых исследованиях продемонстрировано повышение параметров АР при СН по сравнению с контрольной группой [14], но изменения жесткости при разных фенотипах фракции выброса (ФВ) изучены недостаточно [15,16]. Работ, посвященных изучению взаимного влияния параметров ригидности и диастолической функции и вклада повышенной жесткости в прогноз у пациентов с СНсФВ немало, хотя результаты их 55,5 %, central PP ≥ 50 mmHg -in 16,6 %, high AS gradient -in 70,3 %.…”
Section: Introductionunclassified